PUBLIC PRIVATE PARTNERSHIP IN STRENGTHENING THE BASE OF HIGHER EDUCATION IN INDIA - Vinayendra Mani Tripathi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The current situation calls for the expansion of higher education facilities. An effort was made to strengthen the open and distance learning system at the university level when the New Education Policy (1986–1992) was implemented. International assistance was focused more on broadening the foundation of elementary education during the 1990s, nevertheless. Since then, a number of funds have been made available to improve the lower levels of education in developing nations like India. The use of qualified human resources is required in all areas of development in the twenty-first century. From a quantitative standpoint, the higher education system in India enrolls about 2% of the 17–23 year old age cohort. To demonstrate our strength in the area of higher education in a knowledge society, we need to double this number. A few factors prevent government-run or -aided organizations from growing quickly. Although limited finances are anticipated to be a significant hurdle, lack of political will to build the foundation of higher education through government initiatives stands in the way. The bureaucratic system also interferes with the higher education system's ability to operate independently. Delays in product delivery, apathy among the staff, and a top-down, directive governance structure all hinder the system's ability to operate efficiently. Particularly in the domain of professional education, the private unaided systems provide a considerable contribution to the expansion of higher education. Lack of a service-oriented strategy coupled with a profit-driven goal contributes to the exploitation of target populations by offering meager incentives for the employability of its products in niche job markets. In order to promote higher education in its truest sense, neither the government nor the private sector can function well.